A novel influenza A H1N1 clinical manifestations in patients at Chiang Mai university hospital - Romanee Chaiwarith (2018)
Objective: To describe the clinical manifestations of patients affected with a novel influenza A (H1N1 2009) during the pandemic Material and Method: A retrospective study was conducted in patients with influenza-like illness receiving care at Chiang Mai University Hospital between June 1 and September 30, 2009. The inclusion criteria were as follows 1) patients had influenza-like illness that was defined as fever, with cough and/ or sore throat, 2) detection of influenza A H1N1 2009 by real-time polymerase chain reaction (RT-PCR) from nasopharyngeal swabs or throat swabs. Results: Among 278 patients, 150 patients (54.0%) were male and the mean age was 21.4 + 13.1 years (range 1-74). Eightyseven patients (31.3%) were in age group 15-19 years. Fifty-eight patients (20.9%) had underlying diseases and asthma was the most common health problem. The presenting symptoms were cough (dry or productive) (248 patients, 89.2%), fever > 38.0°C (229 patients, 82.4%), sore throat (195 patients, 70.1%), rhinorrhea (126 patients, 45.3%) and myalgia (113 patients, 40.6%). Five patients had co-infection at admission, three patients had dengue hemorrhagic fever, one patient had mycoplasma infection, and the other one with Acinetobacter lwoffii bacteremia. One hundred forty four patients (51.8%) received oseltamivir. Two hundred seventy two patients (97.8%) recovered without complications. One pregnant-woman developed severe pre-eclampsia five days after the first symptom, one patient developed Guillain Barre syndrome 10 days after the first symptoms. Four patients died, all had pneumonia. Conclusion: Younger people were more likely to be infected with influenza A H1N1 2009. The clinical manifestations were similar to the seasonal influenza. However, the mortality rate was much higher, particularly in patients who developed pneumonia. In this study, all patients who died had existing underlying medical conditions.